Reflection of folk song of the Great Patriotic War in the materials of the 1945 expedition by M. Hrynblat - Hulak, Nastassia A. (Journal of the Belarusian State University. Philology, 2020)
The article analyzes the materials of the archival collection of songs of the Great Patriotic War recorded in 1945 in Western Belarus by Moysey Hrynblat – a Belarusian Soviet ethnographer and folklorist. The value of these texts as scientific sources is determined by them being part of a living folk tradition. The materials are approached as a random selection of elements (songs recorded for the 9–15 June 1945 with residents of Hrodna, Lida, Navahrudak, Baranavičy). This sample demonstrates the quality of the original set of elements (repertoire of songs of postwar Western Belarus) significant in the context of research objectives (study of semantics and genre variety of folk wartime art). The songs of the collection are claimed to be mainly lyrical epic works, namely new time modifications of a ballad. New facts of history of collection and studies of folklore in Great Patriotic War enable to avoid unilateral estimates approved by the Soviet folklore studies and expand the problem field of modern science.